Toward Native Web Execution. - Kroeker, Kirk L. (Communications of the ACM, 2009)
The article discusses software projects that are increasing the performance of browser-based applications to the point where such applications are nearing the quality of their desktop counterparts. In improving the performance of the web-based applications, computer scientists have created new methods to improve web-based computing security. Other topics include desktop applications that use computer code created from high-quality compilers and applications that run natively at operating system (OS) levels.